(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This work explores how hydrostatic (all-round) pressure and temperature modify the band structure and the density of states in n-Si⟨Ni⟩ and n-Si⟨Co⟩ samples. Experimental evidence indicates that pressure-driven breakup of nickel- and cobalt-related impurity clusters generates additional localized levels within the band gap and causes a pronounced, multi-fold rise in the resistivity. Incorporating temperature effects on the band-gap width, the carrier effective mass, and the Fermi–Dirac distribution, we propose a theoretical framework describing the density of states g(E,P,T), the free-carrier concentration n(P,T), and the resistivity ρ(P,T) in terms of the deformation (pressure) energy E_def(P) and temperature T. The combined impact of pressure and temperature is discussed qualitatively, demonstrating that increasing temperature progressively smooths the step-like features observed in the ρ/ρ₀(P) dependence.